1989
DOI: 10.1042/bj2640625
|View full text |Cite
|
Sign up to set email alerts
|

Sulphane sulphur in biological systems: a possible regulatory role

Abstract: cess appears to be essential for making the sulphur cyanolysable as evidenced by the acquisition of cyanolysability when ,-mercaptopyruvate is converted to the disulphide; only the latter can give the -S(S)form. This tautomerization can also occur in polysulphides and the lability of the sulphur in polysulphides with n > 3 compared with the stability of dialkyldisulphides (n = 2) again reflects the capacity to tautomerize

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
186
1
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(189 citation statements)
references
References 138 publications
1
186
1
1
Order By: Relevance
“…Following release, hydrogen sulfide can be stored in cells as bound sulfane sulfur that can be released by reducing conditions (44). Bound sulfane sulfur is the major determinant of physiological functions of hydrogen sulfide (45)(46)(47). Recent studies indicate that hydrogen sulfide has diverse effects on cell function including cell survival, hemodynamics, and inflammation (44); however, its role in protein synthesis has not been examined in detail.…”
Section: Discussionmentioning
confidence: 99%
“…Following release, hydrogen sulfide can be stored in cells as bound sulfane sulfur that can be released by reducing conditions (44). Bound sulfane sulfur is the major determinant of physiological functions of hydrogen sulfide (45)(46)(47). Recent studies indicate that hydrogen sulfide has diverse effects on cell function including cell survival, hemodynamics, and inflammation (44); however, its role in protein synthesis has not been examined in detail.…”
Section: Discussionmentioning
confidence: 99%
“…These are briefly described in the next few paragraphs; detailed reviews can be found in Refs. (75,86,134,135,167,168,181,196). The downstream consequences of these initial signaling events on ion channel permeability, transport processes, enzyme activity, or structural proteins are not considered.…”
Section: Mechanism Of H 2 S Signalingmentioning
confidence: 99%
“…Toohey suggested that the malignant proliferation of cells may be related to a deficiency of sulfane sulfur. In fact, the observed defective sulfur metabolism in cancer cells and the anti-cancer effects in vivo of sulfane sulfur compounds may be due to the uncontrolled activity of a set of enzymes normally inactivated by sulfane sulfur (Toohey 1989). Cutting and crushing of garlic cloves induces the release of the vacuolar enzyme alliinase (alliin lyase EC.…”
Section: Introductionmentioning
confidence: 99%